2016
DOI: 10.1089/can.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Regulation of Acute and Anticipatory Nausea

Abstract: Chemotherapy-induced nausea is one of the most distressing symptoms reported by patients undergoing treatment, and even with the introduction of newer antiemetics such as ondansetron and aprepitant, nausea remains problematic in the clinic. Indeed, when acute nausea is not properly managed, the cues of the clinic can become associated with this distressing symptom resulting in anticipatory nausea for which no effective treatments are available. Clinical trials exploring the potential of exogenous or endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
0
9
1
2
Order By: Relevance
“…Parker reports that animal studies have found CBD can suppress nausea and vomiting within a limited dosage range, with the anti-nausea/emetic effects potentially mediated via indirect activation of somatodentritic 5-HT 1A receptors in the dorsal raphe nucleus which reduces release of 5-HT in terminal forebrain areas [ 40 ]. Various animal studies indicate that cannabinoid acids (cannabidiolic acid (CBDA) and tetrahydrocannabinolic acid (THCA)) can suppress nausea [ 179 , 180 , 181 , 182 ], with CBDA 1000 times more potent than CBD in decreasing acute and anticipatory nausea [ 181 ]. In addition, subthreshold doses of CBDA potentiated the anti-nausea effect of Ondansetron (see [ 182 ]).…”
Section: Evidence Of Efficacy Of Cbd In Management Of Cancer and Canc...mentioning
confidence: 99%
“…Parker reports that animal studies have found CBD can suppress nausea and vomiting within a limited dosage range, with the anti-nausea/emetic effects potentially mediated via indirect activation of somatodentritic 5-HT 1A receptors in the dorsal raphe nucleus which reduces release of 5-HT in terminal forebrain areas [ 40 ]. Various animal studies indicate that cannabinoid acids (cannabidiolic acid (CBDA) and tetrahydrocannabinolic acid (THCA)) can suppress nausea [ 179 , 180 , 181 , 182 ], with CBDA 1000 times more potent than CBD in decreasing acute and anticipatory nausea [ 181 ]. In addition, subthreshold doses of CBDA potentiated the anti-nausea effect of Ondansetron (see [ 182 ]).…”
Section: Evidence Of Efficacy Of Cbd In Management Of Cancer and Canc...mentioning
confidence: 99%
“…The endocannabinoid system has shown an important role in the regulation of nausea in preclinical studies. Smoked or orally administered THC appeared to be effective in reducing chemotherapy-induced vomiting and nausea (CINV) in several trials [68].…”
Section: The Medical Indications For Cannabinoidsmentioning
confidence: 99%
“…Some adjuvant drugs (e.g., benzodiazepines and cannabinoids) have a role in CINV control, particularly in the management of anticipatory symptoms and anxiety, 36 , 37 however, the wide spectrum of toxicity (sedation, dizziness, dysphoria, disorientation and hallucinations) limits their routine use in paediatric patients. 38 , 39…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…35 In 2016, MASCC/ESMO recommended acute CINV prophylaxis using a 5-HT3 antagonist for children receiving low emetogenic chemotherapy, and using a 5-HT3 antagonist AE dexamethasone AE aprepitant for children receiving highly or moderately emetogenic chemotherapy. 4 Some adjuvant drugs (e.g., benzodiazepines and cannabinoids) have a role in CINV control, particularly in the management of anticipatory symptoms and anxiety, 36,37 however, the wide spectrum of toxicity (sedation, dizziness, dysphoria, disorientation and hallucinations) limits their routine use in paediatric patients. 38,39 Finally, in CINV control and prevention, a series of complementary, non-pharmacological interventions (e.g.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%